Progress towards enhanced access and use of technology during the COVID-19 pandemic: A need to be mindful of the continued digital divide for many rural and northern communities. Issue 5 (September 2022) - Freeman, Shannon; Marston, Hannah R.; Ross, Christopher; Morgan, Deborah J.; Wilson, Gemma; Gates, Jessica; Kolochuk, Stefani; McAloney, Richard
The COVID-19 pandemic produced unprecedented adoption and deployment of technology in rural and northern areas; however, this expansion widened the digital divide for many. Evidence shows that older adults' use of technology has increased. Coupled with an increasing number of available technologies to enhance healthcare delivery, social engagement, meaningful activities, and support to carers, we are at a crossroads for change. Emerging strategies used by organizations to promote technology and support efforts to bridge and close the digital divide are discussed. In a post-pandemic society, policy-makers can play a critical role to ensure that improvements, efficiency gains, and lessons learned are fully leveraged to reap the benefits of technology use by older adults, care partners, and the healthcare system. Recommendations are given for policy-makers to capitalize on this opportunity to narrow the digital divide for those in rural and northern communities.